Meeting Spiritual Needs to Improve The Quality of Life of Patients in Supervision COVID-19 in Medan - Adventy Riang Bevy Gulo; Edriyani Yonlafado Simanjuntak; Johansen Hutajulu (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2021)
Introduction: Covid-19, a new disease, has been becoming a pandemic. One of the terms in patients exposed to this virus is Patient Under Surveillance. Currently,Covid-19 are under psychological pressure which is one of the factors that affect the patients’ immunity so they need adequate spiritual support from nurses. The purpose of this study is to identify the fulfillment of spiritual needs in improving the quality of life of Covid-19 patients under supervision in Medan. Methods: This type of research is a quantitative study with a correlative approach and a cross sectional study design to determine the fulfillment of the spiritual needs of patients in improving the quality of life of Covid-19 patients under supervision in Medan. Probability random sampling method is used as sampling with simple random sampling technique. There are 40 patients as respondents. A questionnaire contains 14 statements to fulfill the patients’ spiritual needs and 25 statements for the patients’ quality of life using a Likert scale as the instruments. Data analysis with bivariate analysis to identify the fulfillment of spiritual needs in improving the quality of life of Covid-19 patients under supervision in Medan. Chi Square is analyzed using a computer program and used as statistical test. Results: The results of the analysis showed the results of the bivariate test in this study show 19 patients with enough needs, 11 (57.9%) patients who have a good quality of life and 8 (42.1%) patients have a very good quality of life. Among 21 patients with good fulfillment of needs, there are 3 (14.3%) patients have a good quality of life and 18 (85.7%) patients have a very good quality of life. The results of the Chi Square test showed that there is a relationship between patients’ fulfillment and quality of life (p = 0.011). Conclusion: Fulfilling spiritual needs can improve the quality of life of Covid-19 patients under supervision.